Small, Seeding-Competent Huntingtin Fibrils Are Prominent Aggregate Species in Brains of zQ175 Huntington’s Disease Knock-in Mice - Schindler, Franziska; Praedel, Nicole; Neuendorf, Nancy; Kunz, Severine; Schnoegl, Sigrid; Mason, Michael A.; Taxy, Bridget A.; Bates, Gillian P.; Khoshnan, Ali; Priller, Josef; Grimm, Jan; Maier, Marcel; et al. (Frontiers in Neuroscience, 2021)
The deposition of mutant huntingtin (mHTT) protein aggregates in neurons of patients is a pathological hallmark of Huntington’s disease (HD). Previous investigations in cell-free and cell-based disease models showed mHTT exon-1 (mHTTex1) fragments with pathogenic polyglutamine (polyQ) tracts (>40 glutamines) to self-assemble into highly stable, β-sheet-rich protein aggregates with a fibrillar morphology. HD knock-in mouse models have not been extensively studied with regard to mHTT aggregation. They endogenously produce full-length mHTT with a pathogenic polyQ tract as well as mHTTex1 fragments. Here, we demonstrate that seeding-competent, fibrillar mHTT aggregates can be readily detected in brains of zQ175 knock-in HD mice. To do this, we applied a highly sensitive FRET-based protein amplification assay that is capable of detecting seeding-competent mHTT aggregate species down to the femtomolar range. Furthermore, we show that fibrillar structures with an average length of ∼200 nm can be enriched with aggregate-specific mouse and human antibodies from zQ175 mouse brain extracts through immunoprecipitations, confirming that such structures are formed in vivo. Together these studies indicate that small, fibrillar, seeding-competent mHTT structures are prominent aggregate species in brains of zQ175 mice.